Study on the law of artificial crack propagation and fracturing technology in strong heterogeneous conglomerate strata: a case study of the Mahu glutenite in Xinjiang Oilfield. Issue 5 (February 2020) - Duan, Guifu; Tian, Gang; Guo, Dingfei; Zhang, Jingchen; He, Chunming; Yu, Huiyong; Chen, Jin
Abstract: The glutenite reservoir of the Triassic Baikouquan Formation in the Mahu sag with a large amount of resources, is the main block for Xinjiang oilfields and even domestic oil production in recent years. The reservoir is characterized by deeper burial, fewer natural cracks, low fluidity, high pressure coefficient, high horizontal stress difference and special lithology. For these geological problems, researches on fracture extension law, proppant placement law and fracturing technology have been developed to form an integrated volume fracturing technology of heterogeneous glutenite geological engineering. The contributions are as follows:(1) The lithofacies reservoir in Mahu includes matrix support, particle support and mixed support, which makes the conglomerate reservoir have large differences in many respects. The mechanical parameters of granular-supported conglomerate are higher than those of complex-base-supported conglomerate, and the brittleness index is higher.(2) Fracture regularity of glutenite varies greatly at different scales. As the ratio of fracture size to gravel size enlarges gradually, the influence of gravel on fracture extension weakens.(3) The fracture roughness of glutenite has great influence on fluid flow and proppant migration. The sand-laden fluid flows by fingering in small fracture. The crack with larger width is the dominant flow channel and will influence proppant placement.